Improved therapeutic index of an acidic pH-selective antibody. Issue 1 (31st December 2022) - Lee, Peter S.; MacDonald, Katherine G.; Massi, Evan; Chew, Pamela V.; Bee, Christine; Perkins, Padma; Chau, Bryant; Thudium, Kent; Lohre, Jack; Nandi, Pradyot; Deyanova, Ekaterina G.; Barman, Ishita; et al.
ABSTRACT: Although therapeutically efficacious, ipilimumab can exhibit dose-limiting toxicity that prevents maximal efficacious clinical outcomes and can lead to discontinuation of treatment. We hypothesized that an acidic pH-selective ipilimumab (pH Ipi), which preferentially and reversibly targets the acidic tumor microenvironment over the neutral periphery, may have a more favorable therapeutic index. While ipilimumab has pH-independent CTLA-4 affinity, pH Ipi variants have been engineered to have up to 50-fold enhanced affinity to CTLA-4 at pH 6.0 compared to pH 7.4. In hCTLA-4 knock-in mice, these variants have maintained anti-tumor activity and reduced peripheral activation, a surrogate marker for toxicity. pH-sensitive therapeutic antibodies may be a differentiating paradigm and a novel modality for enhanced tumor targeting and improved safety profiles.